Evaluation of end clearance and using stiffeners on gusset plate effect on the compressive performance of diagonal bracing systems - Mussa Mahmoudi Sahebi (Iranian Society of Structrual Engineering (ISSE), 2018)
The braced frame is used in steel structures to confront lateral loads. In Iran, braced frames, especially concentrically braced frames are more commonly used due to their high levels of rigidity and ease and speed of construction. The bracing member of this system bears considerable amounts of load, and thus it needs to be properly connected to the main frame members to display a satisfactory performance. Gusset plates are used to implement such connections. Due to the need for ductility of concentrically braced frames, researchers have conducted extensive research on factors influencing ductility of these structures and especially their connections. The brace end clearance is one of the factors influencing this parameter. It is also possible to influence the connection and frame performances by using stiffeners on gusset plates. This connection is designed to either prevent problems caused to the end-connection through free buckling of a member or reinforcing the gusset plate to reduce damages caused by possible buckling of a member at the connection location. In this research, 5 one-span one-story frames with diagonal braces were modeled in ABAQUS finite element method software. The effects of brace end clearance and effects of stiffeners on gusset plates were studied in the first 2 models and the other 3 models, respectively. First, a buckling analysis was carried out to study brace critical load and the brace effective length coefficient. Afterwards, considering the initial imperfection determined by buckling analysis, the samples were exposed to post-buckling nonlinear analysis and results of the base shear-displacement and stress-strain curves were compared. Comparison results revealed that by considering the brace end clearance recommended by reputable building codes it is possible to increase ductility and prevent early failure of corner joint plates. Proper use of stiffeners also may improve performance of lateral connections and the braced frame.